2014
DOI: 10.3174/ajnr.a3935
|View full text |Cite
|
Sign up to set email alerts
|

Early Basal Ganglia Hyperperfusion on CT Perfusion in Acute Ischemic Stroke: A Marker of Irreversible Damage?

Abstract: BACKGROUND AND PURPOSE: CT perfusion scans are often used in acute stroke evaluations. We aimed to assess the outcome of areas of basal ganglia hyperperfusion on CTP in patients with acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 14 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…The former implies excessive CBF, the second suggests the CBF return to physiologic value, while the last closely relates to a tissue state characterized by a CBF in excess of cellular metabolic demand . Furthermore, hyperperfusion was observed both spontaneously or after revascularization procedures . Some studies associated this phenomenon with rapid clinical recovery or better outcome .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The former implies excessive CBF, the second suggests the CBF return to physiologic value, while the last closely relates to a tissue state characterized by a CBF in excess of cellular metabolic demand . Furthermore, hyperperfusion was observed both spontaneously or after revascularization procedures . Some studies associated this phenomenon with rapid clinical recovery or better outcome .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies associated this phenomenon with rapid clinical recovery or better outcome . On the contrary, other studies have shown that hyperperfusion can lead to brain infarction or hemorrhage . Hyperperfusion was also related with two different uncommon phenomena both with negative outcome referred as cerebral hyperperfusion syndrome, mainly reported after carotid endarterectomy, and reperfusion injury mostly associated with arterial thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations